Proteomic analysis of arylamine N-acetyltransferase 1 knockout breast cancer cells: Implications in immune evasion and mitochondrial biogenesis. (2022) - Hong, Kyung U.; Gardner, Jonathan Q.; Doll, Mark A.; Stepp, Marcus W.; Wilkey, Daniel W.; Benz, Frederick W.; Cai, Jian; Merchant, Michael L.; Hein, David W.
Abstract: Previous studies have shown that inhibition or depletion of N -acetyltransferase 1 (NAT1) in breast cancer cell lines leads to growth retardation both in vitro and in vivo, suggesting that NAT1 contributes to rapid growth of breast cancer cells. To understand molecular and cellular processes that NAT1 contributes to and generate novel hypotheses in regard to NAT1′s role in breast cancer, we performed an unbiased analysis of proteomes of parental MDA-MB-231 breast cancer cells and two separate NAT1 knockout (KO) cell lines. Among 4890 proteins identified, 737 proteins were found significantly ( p  < 0.01) upregulated, and 651 proteins were significantly ( p  < 0.01) downregulated in both NAT1 KO cell lines. We performed enrichment analyses to identify Gene Ontology biological processes, molecular functions, and cellular components that were enriched in each data set. Among the proteins upregulated in NAT1 KO cells, pathways associated with MHC (major histocompatibility complex) I-mediated antigen presentation were significantly enriched. This raises an interesting and new hypothesis that upregulation of NAT1 in breast cancer cells may aid them evade immune detection. Multiple pathways involved in mitochondrial functions were collectively downregulated in NAT1 KO cells, including multiple subunits of mitochondrial ATP synthase (Complex V of the electron transport chain). This was accompanied by a reduction in cell cycle-associated proteins and an increase in pro-apoptotic pathways in NAT1 KO cells, consistent with reported observations that NAT1 KO cells exhibit a slower growth rate both in vitro and in vivo. Thus, mitochondrial dysfunction in NAT1 KO cells likely contributes to growth retardation. Graphical Abstract: ga1 Highlights: NAT1 is frequently upregulated in breast cancer. Its inhibition leads to a decrease in breast cancer cell growth. We performed an unbiased proteomics analysis of parental MDA-MB-231 breast cancer cells vs. NAT1 KO lines. Proteins involved in antigen presentation were up in NAT1 KO cells, indicating they may become prone to immune detection. Proteins involved in oxidative phosphorylation and mitochondrial biogenesis were collectively down in NAT1 KO. Mitochondrial dysfunction, in part, can explain the growth retardation observed in NAT1 KO MDA-MB-231 breast cancer cells.